2018
DOI: 10.12691/ajnr-6-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigate Young Female Reaction Concerning Their Gynecological Examination

Abstract: The aim of this study was to investigate young female reaction concerning their gynecological examination. Design: descriptive study. Setting: This study was conducted at obstetrics and gynecology outpatient clinic at Mansoura university hospital, Egypt. Subjects: two hundred and three young female. Sample type: purposive sample. Tools: An interviewing questionnaire schedule, emotional stress reaction questionnaire, visual analogue scale and immediately post gynecological examination assessment. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The question of obstetrician-gynecologists gender provoked feelings of embarrassment [ 32 ] that can be attributed to cultural, traditional, and religious undercurrents in Egyptian society. These constitute a barrier against a female exposing her genitals to a male gynecologist or obstetrician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of obstetrician-gynecologists gender provoked feelings of embarrassment [ 32 ] that can be attributed to cultural, traditional, and religious undercurrents in Egyptian society. These constitute a barrier against a female exposing her genitals to a male gynecologist or obstetrician.…”
Section: Discussionmentioning
confidence: 99%
“…The structured questionnaire contained 4 sections: (1) “Trust in Physician Scale” (TPS) [ 31 ], with 11 items on a scale designed to measure interpersonal patient trust in physicians relating to primary care services; (2) The SERVQUAL quality models [ 32 ], which contain five dimensions of service quality; (3) 5Qs model, a comprehensive model of patient satisfaction with healthcare providers [ 33 ]; and (4) socio-demographic questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan et al (2018) who had revealed that majority among the present studied sample had incorrect knowledge concerning definition, importance, complication & preparation [39]. Similarly, Freyens et al(2017) reported that the majority of women in Egypt had incorrect knowledge regarding reproductive issues because culture and tradition prevent them from discussing these issues of reproductive and gynecological health [40].…”
mentioning
confidence: 84%
“…The total score increased from 4.3 to 4.9 although the difference did not reach statistical significance (p=0.13). [39] Moreover, Hilden et al (2003) stated that most women felt emotional discomfort regarding the gynecologic examination. [42] In the present patients, there was a highly statistically significant relationship between the total knowledge of the studied sample about gynecological examination at the post of an instructional supportive guideline and their education level at (P<0.01).…”
Section: Figure (1): Distribution Of the Studied Sample According To ...mentioning
confidence: 99%